A study on a novel two-body floating wave energy converter. (15th January 2017) - Dai, Youming; Chen, Yangzhi; Xie, Longhan
Abstract: This paper proposes a novel wave energy converter (WEC), which is needed for monitoring the marine environment. The converter is composed of two oscillating bodies: a floating sphere connected to a heavy submerged sphere using a tight rope and a power take off (PTO) system mounted in the floater. Energy is converted from the relative motion between the differently oscillating bodies caused by the action of the waves. The model was first tested in the frequency domain to optimize the geometry and mechanical parameters, and subsequently, a time domain model was built for simulation of a multi-DOF motion system. In the frequency domain research, a constraint was first added to the two-body WEC to address the problem of the small value of the optimized PTO damping. The state space approximation method was employed during the time domain simulation, and external forces acting on the bodies due to the tight rope were deduced. The motions of the system and power absorbed by the converter under regular and irregular waves were analyzed in detail. Finally, experiments were conducted on a scaled model, and the results show that the total power efficiency was more than 20%. Highlights: We propose a novel WEC and introduce its basic structure and working priciple. A constrain is first added to the WEC, and a strong solution is obtained. Forces acting on bodies are deduced, and a time-domain simulation is employed. Experiments are conducted and results are in accord with the numerical analysis.